Effects of tamarindus indica fruit pulp extract on abundance ofHepG2 cell lysate proteins and their possible consequential impact on metabolism and inflammation - Chong, U.R.W.; Abdul-Rahman, P.S.; Abdul-Aziz, A.; Hashim, Onn Haji; Junit, Sarni Mat (Hindawi Publishing Corporation, 2013)
The fruit pulp extract of Tamarindus indica has been reported for its antioxidant and hypolipidemic properties. In this study, the methanol extract of T. indica fruit pulp was investigated for its effects on the abundance of HepG2 cell lysate proteins. Cell lysate was extracted from HepG2 cells grown in the absence and presence of the methanol extract of T. indica fruit pulp. Approximately 2500 spots were resolved using two-dimensional gel electrophoresis and the abundance of 20 cellular proteins was found to be significantly reduced. Among the proteins of reduced abundance, fourteen, including six proteins involved in metabolism (including ethanolamine phosphate cytidylyltransferase), four mitochondrial proteins (including prohibitin and respiratory chain proteins), and four proteins involved in translation and splicing, were positively identified by mass spectrometry and database search. The identified HepG2 altered abundance proteins, when taken together and analyzed by Ingenuity Pathways Analysis (IPA) software, are suggestive of the effects of T. indica fruit pulp extract on metabolism and inflammation, which are modulated by LXR/RXR. In conclusion, the methanol fruit pulp extract of T. indica was shown to cause reduced abundance of HepG2 mitochondrial, metabolic, and regulatory proteins involved in oxidative phosphorylation, protein synthesis, and cellular metabolism.